Work stress and competency among radiology residents: the mediating effect of resilience - Shen, Lijun; Lu, Yuanmei; He, Yanrong; Wang, Peicheng; Chen, Yanhua; Li, Hange; Yang, Zhenghan; Zhang, Jingfeng; Wang, Zhenchang; Jiang, Maoqing; Zheng, Jianjun; Zhu, Jiming (Frontiers in Public Health, 2024)
Background Competency of health professionals stands as a fundamental element in ensuring the quality of care. Notably, work stress and resilience are found to be associated with competency of health professionals. However, the role of resilience between work stress and competency remains unexplored. This study aims to investigate competency, work stress and resilience of radiology residents, and to examine the mediating effect of resilience. Methods A cross-sectional survey was conducted among 3,666 radiology residents from 31 provinces of China in 2021. The diagnostic radiology milestones were used to measure the competency. Results of work stress and resilience were derived from self-reports and assessment of the Connor Davidson Resilience Scale (CD-RISC) respectively. To examine the association between work stress, resilience, and competency, Spearman correlation analysis and hierarchical linear regression were employed. The mediating effect of resilience was tested by bootstrapping analysis. Results Descriptive statistics show that the average score (mean ± SD) of work stress, competency and resilience among radiology residents were 1.55 ± 1.53 (range from 0 to 6), 28.14 ± 13 (range from 0 to 81) and 5.97 ± 1.92 (range from 0 to 8), respectively. Work stress was negatively associated with competency (β = −0.51, p < 0.001) and resilience (−0.57, p < 0.001). In particular, resilience mediated the relationship between work stress and competence, and the total mediating effect was −0.49 (= − 0.57 * 0.86), accounting for 49.06% of the total effect. Conclusion Work stress is a significant contributor to competence among radiology residents. Resilience significantly mediated the association. This study highlights incorporating resilience training courses into the standardized residency training program to reduce intensive work stress and promote competency of radiology residents.